Optimalisasi Produk Tahu Menggunakan Program Linear Metode Simpleks - Amin harahap; Anisa riyani; Andini febry hijriyati; Junida andrrea sapitr; Mayliawati Mayliawati (Journal of Innovative and Creativity, 2026)
The tofu industry is a type off small and medium enterprise that requires optimal production management to maximize profits generated with limited resources.This study aims to optimize tofu production volume using a linear programming approach with the simplex method.The matematichal model developed in this study is in the form of an objective funcition ti maximize profits with limitations such as limited raw materials raw materials,labor,andlimited production capacity.The data used is tofu production data analyzed quantitatively. The model is solved using the simplex method to obtain an optimal solution.